IMPACT DE L’AGE DE SOUCHES ET DE DOSES CROISSANTES DE FUMIER DE VACHE SUR LA TAILLE DES REPOUSSES ET SUR LA TENEUR EN PROTEINE BRUTE DES FEUILLES DE BRACHIARIA MUTICA (L) A KISANGANI - MARCEL, DJUMA MASUDI (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
The impact of the age of stumps and increasing doses of cow manure on the size of shoots and on the content in raw protein of Brachiaria mutica (L) to Kisangani, was studied on land and to the laboratory in view to determine the best period (age of stumps) where one will be able to profitably grazed animals and the dose of cow manure capable to produce leaves highly proteinic. Hypotheses to verify were the following: The size of Brachiaria mutica’s (L) shoots would increase with the age of the mother stump; The size of repulse Brachiaria mutica’s (L) shoots would increase with doses of applied of cow manure to the mother stump; The rate of raw protein in leaves of repulse Brachiaria mutica’s (L) shoots would increase with doses of cow manure ; The rate of raw protein in leaves of repulse Brachiaria mutica’s (L) shoots would decrease the age of mother stump. The gotten resultants reveal that: The growth of shoots seems to depend on other factors that the age of the stump mother and doses of cow manure applied. The experience showed that to 40 days, stumps give a better rate of raw protein Finally hypotheses of this research have not been verified.